2021
DOI: 10.1039/d0ma00718h
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped few-layer graphene encapsulated Pt-based bimetallic nanoparticles via solution plasma as an efficient oxygen catalyst for the oxygen reduction reaction

Abstract: A superior durability of N-doped few-layer graphene shell for Pt-based bimetallic core protection by solution plasma process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 70 publications
5
29
0
Order By: Relevance
“…They reported that, as with bulk graphite, the obtained graphene nanosheet had a layer distance of around 0.34 nm. The same results were also obtained when Phan et al performed experiments for the nitrogen-doped metal nanoparticle covered in a few graphene layers by using solution plasma with a 1.0 µs pulse width and a 30 kHz repetition frequency [114].…”
Section: 4 For Peersupporting
confidence: 70%
See 1 more Smart Citation
“…They reported that, as with bulk graphite, the obtained graphene nanosheet had a layer distance of around 0.34 nm. The same results were also obtained when Phan et al performed experiments for the nitrogen-doped metal nanoparticle covered in a few graphene layers by using solution plasma with a 1.0 µs pulse width and a 30 kHz repetition frequency [114].…”
Section: 4 For Peersupporting
confidence: 70%
“…It seems that the carbon materials possessed the multi-walled carbon nanocapsule with walls consisting of several graphene layers ranging from two to six layers. The gaps between the atomic layers in these carbon products were around 0.34 nm, where the 0.34 nm distance can be associated with the lattice spacing of graphene layers [111][112][113][114]. This revealed that the carbon materials could be generated by applying the high-voltage discharge plasma on the glycine solution through deamination and decarboxylation reactions [40][41][42][43]98].…”
Section: 4 For Peermentioning
confidence: 99%
“…Here, a brief explanation of the electrical discharge under an aqueous solution (e.g., electrical breakdown, formation of reactive species, and influencing factors) in the SPP is provided. [14,29,30], (b) [31,32], (c) [27,[33][34][35], (d) [36][37][38], (e) [15,22], and (f) [39][40][41][42]. [31,32], (c) [27,[33][34][35], (d) [36][37][38], (e) [15,22], and (f) [39][40][41][42].…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 99%
“…The distance between the tips of electrodes in the HCl solution increased from 0.1 mm to 0.17 mm, while 0.12 mm and 0.15 mm were observed in the KCl and KOH solution, respectively. Accordingly, it suggested that acidity has a significant influence on the sputtering of metal electrodes in the SPP, which is considered as an advantage for the synthesis of metal-based nanoparticles without using precursors and reducing agents [ 32 , 38 , 57 ]. Furthermore, the investigation on the formation of • OH was also conducted via the time-resolved optical emission measurement at various time delays to the positive voltage pulse in the range of 0–38 μs.…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 99%
See 1 more Smart Citation